The Analysis Study of Comparison of Chest Tube Drainage vs Conservative Management of Pneumothorax: A Comprehensive Systematic Review - Mochamad Riwayanto Akbar; Fika Sri Yuliandari; Antonius Nirmala (International Medical Journal Corp. Ltd, 2024)
Background: The management of pneumothorax significantly across different clinical guidelines, reflecting ongoing uncertainty in the optimal approach to treatment. Recent research has highlighted the potential benefits of conservative management compared to surgical approach. This systematic review aims to compare the outcomes of conservative management and chest tube drainage in the treatment of pneumothorax by analyzing available studies of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Conservative management of pneumothorax, particularly in clinically stable patients, has shown effectiveness comparable to chest tube drainage, with benefits such as shorter hospital stays and fewer complications. However, careful patient selection and further trials are needed to confirm its long-term safety and efficacy.